Optimalisasi Administrasi Ketatausahaan Sekolah Era Society 5.0 : Studi Komprehensif tentang Konsep, Proses, dan Keterlibatan - Fina Olivia; Fatma Maulida; Ahmad Sabri; Rully Hidayatullah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2024)
This journal examines the optimization of school administrative management within the context of Society 5.0, focusing on the concepts, processes, and teacher involvement in educational administration. The research aims to identify the challenges and opportunities faced in administrative management and provide recommendations to enhance the efficiency and effectiveness of administrative services in schools. Through a literature review methodology, this study analyzes relevant literature on administrative management, best practices in educational management, and theories underlying teacher involvement in administrative processes. The findings indicate that optimizing administrative management in the Society 5.0 era requires the integration of advanced technologies such as artificial intelligence, the Internet of Things, and big data into educational information management processes. Teacher involvement in administration is crucial for creating a better learning environment and supporting the achievement of educational goals. By leveraging technology and adopting more collaborative approaches, schools can improve the quality of administrative services and responsiveness to community needs in the digital age.